Significance of Post-Operative Free Gas in Laparoscopic Surgery: Significance of Post-Operative Free Gas in Laparoscopic Surgery - Parekh, Brijesh; Modi, Ronak R.; Patel, Asit V. (National Journal of Integrated Research in Medicine, 2018)
Laparoscopic surgery is routinely performed nowadays at all centers with better patient outcome. But, in post-operative period, if any hollow viscus perforation occurred; either due to underlying pathology, or may be due to iatrogenic injury during laparoscopic surgery, can be missed in early stage due to pneumo-peritoneum created during laparoscopic surgery. We document our study on 50 patients to see patient outcome and time duration of resolution of pneumoperitoneum. We’ve done serial abdominal/chest x-rays in standing position from post-operative day 1 till the resolution of pneumo-peritoneum, in various laparoscopic procedures. On an average, CO2 used during total duration of surgery was 98.7 liter of CO2 in appendicectomy, 136.9 liter of CO2 in cholecystectomy & 140 liter of CO2 in hernioplasty. On observation, we didn’t find pneumo-peritoneum on x-rays, even on post-operative day 1. In one patient, iatrogenic intra-operative cautery burn was present on anterior wall of stomach during laparoscopic cholecystectomy. But, on post-operative day-1, no pneumo-peritoneum was found. And even on serial abdominal/ chest x-rays on subsequent postoperative days also, we didn’t find any free gas. That patient recovered better. On conclusion, serial study of abdominal/chest x-rays in standing position during post-operative period following laparoscopic surgery is a better tool, to diagnose any hollow viscera perforation at the earliest, or on the other hand, to rule out any suspected hollow viscus perforation. [Brijesh P NJIRM 2017; 8(4):35-37]